The Nexus of Green HRM and Organizational Performance with a Moderation of Sustainable Leadership: From the Perspective of HR Managers - Zafar, Imran; Ejaz, Khurram; Gul, Saliha (Journal of Business & Tourism, 2024)
The study intends to examine the effect of green HRM on organization performance with moderating role sustainable leadership. The population of the study consists of HR managers working in the Small and Medium Enterprises (SMEs) of Khyber Pakhtunkhwa (KP) Pakistan. The sample was calculated using the GPower sample size formula for unknown population. The Self-administered questionnaires were used for collection of data from HR managers working in SMEs. For the analysis, SPSS Hayes Process was applied for the direct and indirect paths. The findings showed that green T&D, green employee relations, green recruitment and selection, green performance management, and sustainable leadership have a positive impact on organizational performance. The moderating results showed that sustainable leadership moderates the relationship in green training and development, green performance management, green recruitment and selection, green employee relations, and organizational performance. The results further reported that sustainable leadership moderates the above relationships except for the moderating role of sustainable leadership in the association between green compensation and organizational performance. The study has theoretical, methodological, and applied implications for a variety of stakeholders such as regulatory bodies, top management of the SMEs, industry experts and academia to implement green practices specifically in developing countries.